KELAYAKAN FINANSIAL USAHA PENGOLAHAN UBI KAYU MENJADI TIWUL INSTAN DI KABUPATEN LAMPUNG TIMUR. - Ainul Mardliyah; Supriyadi Supriyadi (Politeknik Negeri Lampung., 2018)
This study aims to: 1) Analyze the feasibility of cassava processing business into instant tiwul (KWT Tani Hidup) in Wonosari Village Pekalongan District East Lampung Regency, 2) Know the income of cassava processing into instant tiwul (KWT Tani Hidup) in Wonosari Village Pekalongan District East Lampung Regency. The method of analysis used for the first purpose is financial analysis such as NPV, IRR, Payback Period (PP), Net B / C, and BEP. The second purpose used income analysis. Research location in Wonosari Village Pekalongan District East Lampung Regency. The results of this research can be summarized as follows: 1) Cassava processing business into instant tiwul (KWT Tani Hidup) in Wonosari Village Pekalongan District East Lampung Regency is feasible to be developed and profitable when viewed from financial feasibility from Net Present Value (NPV), worthy business with a positive NPV value is Rp 38,118,538; Internal rate of return (IRR) is 98%; Gross Benefit Ratio (Gross B/C) is 1.71; Net B/C is 3.92; Profitability ratio (PR) is 1.69; Payback period (PP) is 0.1; and BEP is 1.31 ; 2) Instant tiwul business income (KWT Tani Hidup) in Wonosari Village Pekalongan District East Lampung Regency in one month is Rp. 4.460.083 / month.